2018
DOI: 10.1073/pnas.1722686115
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intrathecal orexin delivery inhibits cataplexy in a murine model of narcolepsy

Abstract: Narcolepsy-cataplexy is a chronic neurological disorder caused by loss of orexin (hypocretin)-producing neurons, associated with excessive daytime sleepiness, sleep attacks, cataplexy, sleep paralysis, hypnagogic hallucinations, and fragmentation of nighttime sleep. Currently, human narcolepsy is treated by providing symptomatic therapies, which can be associated with an array of side effects. Although peripherally administered orexin does not efficiently penetrate the blood-brain barrier, centrally delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…33 A recent study showed that slow infusion of orexin delivered via a chronically implanted intrathecal catheter at the upper lumbar level in ORX knockout mice decreased cataplexy and sleep-onset REM sleep with unchanged sleep/wake states both quantitatively and qualitatively. 45 This study supports the concept of chronic intrathecal ORX delivery through an implantable pump as a potential therapy for refractory patients with NT1. A noninvasive method via intranasal administration of ORX (a method targeting drugs to the brain along the olfactory and trigeminal neural pathways) could also be of interest, with few preclinical and clinical data.…”
Section: Drugs In Developmentsupporting
confidence: 80%
See 1 more Smart Citation
“…33 A recent study showed that slow infusion of orexin delivered via a chronically implanted intrathecal catheter at the upper lumbar level in ORX knockout mice decreased cataplexy and sleep-onset REM sleep with unchanged sleep/wake states both quantitatively and qualitatively. 45 This study supports the concept of chronic intrathecal ORX delivery through an implantable pump as a potential therapy for refractory patients with NT1. A noninvasive method via intranasal administration of ORX (a method targeting drugs to the brain along the olfactory and trigeminal neural pathways) could also be of interest, with few preclinical and clinical data.…”
Section: Drugs In Developmentsupporting
confidence: 80%
“…Orexin 45 This study supports the concept of chronic intrathecal ORX delivery through an implantable pump as a potential therapy for refractory patients with NT1. A noninvasive method via intranasal administration of ORX (a method targeting drugs to the brain along the olfactory and trigeminal neural pathways) could also be of interest, with few preclinical and clinical data.…”
Section: Drugs In Developmentsupporting
confidence: 71%
“…Since the peptides do not readily cross the blood-brain barrier, oral or intravenous (IV) administration routes are excluded. Intrathecal administration of Hcrt-1 is effective in treating cataplexy in narcoleptic Hcrt-KO mice [114] and may be a viable option in human narcolepsy, although it would require a combination of surgery and delivery device implantation.…”
Section: Hcrt-r Agonistsmentioning
confidence: 99%
“…In particular, either intrathecal or intravenous delivery of hypocretin or an analogue can abolish cataplexy 32. There are considerable logistical problems in developing a suitable oral compound for human administration although early animal model data look promising 33…”
Section: Treatmentmentioning
confidence: 99%